Feed Additives used in Nutrition and Improve the Poultry Performance and Health: A review - Abbas, Basim Aboud; Nurdianti, Risma Rizkia (The Iraqi Journal of Veterinary Medicine, 2025)
An approach to increase the efficiency of the poultry industry is to supplement the feed additives in diets to enhance growth rates, optimize egg production, mitigate disease prevalence, and improve feed utilization. Primary constituents of poultry diets incorporate cereal grains, predominantly corn, along with wheat, barley, sorghum, and other grains. Additionally, a predominant protein source e.g. soybean meal is utilized, although alternative protein sources, both of animal and plant origin, exist. Beyond these components, the feed nutritional quality is influenced by factors such as presentation, microbial contamination, the presence of antinutritional substances, digestibility, palatability, and intestinal health. A variety of feed additives are available to address these considerations. Particularly, the commercialization of feed additives requires approval through rigorous scientific evaluation, ensuring their lack of adverse effects on human and animal health, as well as the environment. Several feed ingredients formulated in chicken diets show antinutritional properties, limiting their applicability. To fulfill energy requirements and enhance poultry health, it is necessary to develop commercially viable alternatives to existing feed resources, emphasizing safety and cost-effectiveness. This review observed diverse strategies for the utilization of feed additives within conventional poultry production systems, aiming to enhance growth, optimize egg production efficiency, and prevent disease outbreaks.